2020
DOI: 10.3390/app10176101
|View full text |Cite
|
Sign up to set email alerts
|

Termite Resistance of Furfuryl Alcohol and Imidacloprid Treated Fast-Growing Tropical Wood Species as Function of Field Test

Abstract: In general fast-growing tree species harvested at a young age has substantial amount of sapwood. It also contains juvenile wood, which has undesirable inferior physical and mechanical properties. Having sapwood and juvenile wood in the trees makes them very susceptible to be attacked by biological deterioration specifically termites in a tropical environment. The main objective of this study was to investigate the termite resistance of four fast-growing Indonesian wood species treated with furfuryl alcohol and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…And it was found that furan ring is a key pharmacophore for many active natural-products insecticidal agents such as toosendanin and limonin (Xiang et al 2018). In addition, furfuryl alcohol significantly impacted the resistance against the termite of fast-growing tropical wood (Hadi et al 2020) and also resistance to decay fungi of Masson pine wood (Li et al 2015). It can be concluded that the sucrose-ADP particleboard has good biological durability against deterioration organisms such as termites and wood decay fungi, similar to that of particleboards made with synthetic adhesives.…”
Section: Termite and Decay Resistancementioning
confidence: 90%
“…And it was found that furan ring is a key pharmacophore for many active natural-products insecticidal agents such as toosendanin and limonin (Xiang et al 2018). In addition, furfuryl alcohol significantly impacted the resistance against the termite of fast-growing tropical wood (Hadi et al 2020) and also resistance to decay fungi of Masson pine wood (Li et al 2015). It can be concluded that the sucrose-ADP particleboard has good biological durability against deterioration organisms such as termites and wood decay fungi, similar to that of particleboards made with synthetic adhesives.…”
Section: Termite and Decay Resistancementioning
confidence: 90%
“…This indicates that furfurylation and GMA treatments can increase the resistance of short-rotation teaks to termite attacks. Other studies have also reported that furfurylation treatment can increase resistance to termite attacks, as indicated by a decrease in the weight loss value (Hadi et al, 2020(Hadi et al, , 2021. Furfurylation involves a chemical reaction between the FA polymer and wood components, namely, the formation of bonds between FA polymers and lignin (Barsberg and Thygesen, 2017: Shen et al, 2021: Martha et al, 2021a.…”
Section: Resistance Against Subterranean Termitementioning
confidence: 98%
“…Regarding termites, several studies have shown that furfurylated wood can withstand these [91,[115][116][117][118]. However, for these studies nothing is mentioned about possible leaching of the wood samples prior to the termite feeding trials.…”
Section: Biodeteriorationmentioning
confidence: 99%